Производительность труда как показатель эффективности производственной деятельности - Ярчук, Ангелина Владимировна; Ярчук, Ангеліна Володимирівна; Yarchuk, Anhelina (Мелітополь: ТДАТУ, 2014)
RU: В статье рассматриваются вопросы необходимости роста производительности экономической системы. Экономический кризис обостряет проблемы, без решения которых не удается повышение производительности труда из-за технической отсталости. Производительность труда, которая является фактором роста производства продукции, может быть повышена только при учете тех внутренних факто-ров, которые зависят от уровня развития наукоёмких отраслей. В то же время, со стороны государства должны быть приняты меры по повышению конкурентоспособности отечественной продукции на внутреннем и внешнем рынке, стабилизации инвестиционного потенциала украинской экономики. EN: Statement of the problem. Productivity is a key indicator of labor resources in the enterprise, the industry in the state. This is a summary indicator in the analysis of personnel activity, determines the efficiency of the enterprise. An important stage of the analytical work for the company is finding ways to increase productivity. From the level and the dynamics of productivity in different degree, all major indicators of production efficiency. The dynamics of labor productivity depends on such an important indicator as the cost of production. In this thorough and in-depth analysis of the dynamics of labor productivity. The results of the analysis are identified reserves of productivity growth, the measures they use and determined the effectiveness of these activities. Results: labour productivity is determined by the productive power of labour, the level of productivity depends on the development of the means of production and technical capabilities; productivity growth leads to a reduction of all types of costs. Increasing productivity is one of the conditions for reducing the costs of production, improve product quality, an important prerequisite for the appreciation of the nominal and real wages, living standards and reduce inflation in the country, a prerequisite of growth of production of competitive products, development, production and GDP growth Conclusions: the level and rate of growth determine the efficiency of the national economy, the volume and the increase of national income; to increase productivity in need of modernization of the economy: the development of industries with high value-added IT-sphere, the space industry, nanotechnology and so on , hence increasing productivity and as a consequence economic growth of Ukraine. Thus, overcoming the economic crisis in the country is possible only under condition of increasing the efficiency of social labor.
Keywords: производительность труда; эффективность; экономическая система; живой труд; овеществлённый труд; productivity; efficiency; economic system; living labor; embodied labour